Pengaruh Sikap Petani terhadap Partisipasi Program Kartu Tani di Desa Randangmulya, Kecamatan Pedes, Kabupaten Karawang - Makhrus, Muhammad Nabil Hisyam; Sam’un, Mohamad; Melani, Ana (Paspalum: Jurnal Ilmiah Pertanian, 2024)
Farmers in Rangdumulya Village use the Farmer’s Card Program as a 'bridge' in farming because it is useful for redeeming subsidized fertilizers, borrowing People's Business Credit, saving at the Bank, and selling the harvest to Bulog. However, participation still experiences several obstacles. This study aims to describe attitudes and participation, as well as the effect of attitudes on participation in the Farmer’s Card Program simultaneously and partially. This is a mixed-method research in which 45 respondents participated in proportional sampling. Data were obtained primary and secondary through observation, interviews, questionnaires, and literature studies. Data analysis used interval width test and multiple linear regression. The results showed that 60% of farmers had a supportive attitude towards the Farmer Card Program but the participation level of 68.9% of farmers was still low. The results of the simultaneous influence analysis showed that farmers' cognitive, affective, and conative attitudes had a significant effect on participation in the Farmer Card Program. On the other hand, partially, farmers' cognitive and conative attitudes have a positive and significant effect on participation in the Farmer Card Program, but their affective attitudes have a negative and insignificant effect